Plutarcho požiūris į išsilavinusias moteris kūriniuose Coniugalia praecepta ir Consolatio ad uxorem - Voinič, Monika (Literatūra, 2010)
The article aims to establish the attitude, or attitudes, towards educated women and women in general that Plutarch reveals in his moral treatises Coniugalia praecepta and Consolatio ad uxorem. Secondary aim of this articles is to determine, what does he say explicitly or implicitly about educated women and in particular their moral and intellectual aptitude, as well as to ascertain if there is a harmony between Plutarch’s explicit declarations and the implicit message in the above treatises.It should be accentuated that the image of Plutarch as the advocate of women has been modified in recent studies. However it is hardly possible to depict Plutarch as the “misogynist”, a man who with such elegance defends love between man and woman and has such a high respect for marriage, which he regards as an institution based upon the cooperation of both husband and wife.However it should be highlighted that Plutarch by adopting platonic stoic opinion that educated woman can be equal to man, combining it with traditional classical ideal of woman, creates his own unique portrait of an ideal woman. His ideal woman is intelligent, educated, wise, but also modest, obedient and admitting the superiority of men. Plutarch’s appraisal of the marital love and the accentuation of education importance is a unique phenomenon in Greek literature, simultaneously highlighting Plutarch’s uniqueness.However, according to Plutarch, women are inferior as such, but once they accept their inferiority, they can be regarded as equal to men in regard to moral strength. In Plutarch’s opinion, women are not morally depraved unless they transgress the rules of their sex and strive to achieve privileges reserved for men.